Effect of particle size on hydroxyapatite crystal-induced tumor necrosis factor alpha secretion by macrophages - Nadra, Imad; Boccaccini, Aldo R.; Philippidis, Pandelis; Whelan, Linda C.; Mccarthy, Geraldine M.; Haskard, Dorian O.; Landis, R. Clive (Atherosclerosis, 2008)
Macrophages may promote a vicious cycle of inflammation and calcification in the vessel wall by ingesting neointimal calcific deposits (predominantly hydroxyapatite) and secreting tumor necrosis factor (TNF)α, itself a vascular calcifying agent. Here we have investigated whether particle size affects the proinflammatory potential of hydroxyapatite crystals in vitro and whether the nuclear factor (NF)-κB pathway plays a role in the macrophage TNFα response. The particle size and nano-topography of nine different crystal preparations was analyzed by X-ray diffraction, Raman spectroscopy, scanning electron microscopy and gas sorbtion analysis. Macrophage TNFα secretion was inversely related to hydroxyapatite particle size (P = 0.011, Spearman rank correlation test) and surface pore size (P = 0.014). A necessary role for the NF-κB pathway was demonstrated by time-dependent IκBα degradation and sensitivity to inhibitors of IκBα degradation. To test whether smaller particles were intrinsically more bioactive, their mitogenic activity on fibroblast proliferation was examined. This showed close correlation between TNFα secretion and crystal-induced fibroblast proliferation (P = 0.007). In conclusion, the ability of hydroxyapatite crystals to stimulate macrophage TNFα secretion depends on NF-κB activation and is inversely related to particle and pore size, with crystals of 1-2 μm diameter and pore size of 10-50 Å the most bioactive. Microscopic calcific deposits in early stages of atherosclerosis may therefore pose a greater inflammatory risk to the plaque than macroscopically or radiologically visible deposits in more advanced lesions. © 2007 Elsevier Ireland Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.effect
Keywords: Atherosclerosis pathophysiology; Calcification; Inflammation; Macrophage